Cool nail art - Lee, Hannah (Cincinnati, Ohio Fons & Porter, 2014)
"Hannah Lee, creator of the YouTube Channel Hannah Rox Nails, shares more than thirty new nail designs in 'Cool Nail Art'. With tips on how to prep your manicure, clear step-by-step instructions and easy-to-use tools, you can create fabulous nail art designs in your own home."--back cover.
Introduction -- Before you begin -- Dotted and decaled nail art -- Sponged and taped nail art -- Freestyle nail art -- Resources -- Index -- Dedication and acknowledgments -- About the author.
Includes index.
Keywords: Nail art (Manicuring); Fingernails; Manicuring; Beauty, Personal